A Randomized Controlled Trial to Evaluate the Clinical Effectiveness of 3D-Printed Orthosis in the Management of Adolescent Idiopathic Scoliosis. Issue 1 (1st January 2022) - Lin, Yangmin; Cheung, Jason Pui Yin; Chan, Chi Kwan; Wong, Sidney Wing Fai; Cheung, Kenneth Man Chee; Wong, Martin; Wong, Wun Ching; Cheung, Prudence Wing Hang; Wong, Man Sang
Abstract : Study Design: Prospective randomized controlled trial. Objective: To compare clinical effectiveness and quality of life (QoL) of the 3D-printed orthosis (3O) and conventional orthosis (CO) for adolescent idiopathic scoliosis (AIS). Summary of Background Data: Using 3D printing technology to design and fabricate orthoses to manage AIS aiming to improve in-orthosis correction and patients' compliance that are considered essential factors of effective treatment. Clinical evaluation was conducted to study the effectiveness of this innovative method. Methods: Thirty females with AIS who met the criteria (age 10–14, Cobb 20–40°, Risser sign 0–2, ⩽12 months after menarche) were recruited. Subjects were randomly allocated to the 3O group (n = 15, age 12.4, Cobb 31.8°) and CO group (n = 15, age 12.0, Cobb 29.3°). All patients were prescribed for full-time wearing (23 hours/d) and follow-up every 4 to 6 months until bone maturity. Compliance was monitored by thermosensors, while QoL was assessed using three validated questionnaires. Results: Comparable immediate in-orthosis correction was observed between 3O (−11.6°, P < 0.001) and CO groups (−12.9°, P < 0.001). In the QoL study via SRS-22r, the 3O group got worse results after 3 months in aspects of function, self-image, and mental health (−0.5, −0.6, −0.7, P < 0.05) while the CO group had worse results in aspects of self-image and mental health (−0.3, −0.3, P < 0.05). No significant difference was found in QoL assessments between groups. After 2 years of follow-up, 22 patients were analyzed with 4 dropouts in each group. Comparable angle reduction was observed in both groups (3O: −2.2°, P = 0.364; CO: −3.5°, P = 0.193). There was one subject (9.1%) in the 3O group while two subjects (18.2%) in the CO group had curve progression >5°. Daily wearing hours were 1.9 hours longer in the 3O group than the CO group (17.1 vs. 15.2 hours, P = 0.934). Conclusion: The 3O group could provide comparable clinical effects as compared with the CO group while patients with 3O showed similar compliance and QoL compared to those with CO. Level of Evidence: 1 Abstract : A prospective RCT was conducted to compare the treatment effectiveness of the 3D-printed orthosis and the conventional orthosis in the management of adolescent idiopathic scoliosis. The 3D-printed orthosis could provide similar clinical effectiveness and quality of life influence as compared with the conventional orthosis.